(untitled) (Journal of actual problems of jurisprudence, 2020)
The article represents the result of the conducted study on evaluation of evidence as an element of the proof process, consisting of logical activities to determine the relevance, admissibility, reliability and sufficiency of evidence. The article illustrates a scientific and theoretical analysis of the concept of evaluation of evidence in criminal proceedings, as well as the results of a comparative legal study of issue regulatory issues (questions) related to evaluation of evidence in criminal procedure legislation in some foreign countries. Evaluation of evidence consists of the following features: relevance of evidence (its relation to the subject of proof); admissibility of evidence (legality of obtaining it); reliability of evidence (truth, absence of reasonable doubt); sufficiency of evidence (the ability of a set of evidence to justify a decision). The court, the prosecutor, the investigator, and the interrogator evaluate evidences on an internal conviction based on the aggregate evidences available in a criminal case, guided by the law and conscience. Scientific-methodological basis are the laws of the Republic of Kazakhstan, the criminal code, the criminal procedure code of Kazakhstan, as well as the works of famous scientists processualist from Kazakhstan and foreign countries. Key words: proof, process of proof, subject of proof, evaluation of evidence, relevance, admissibility, evidentiary law.